Analgesic effects of mambalgin peptide inhibitors of acid-sensing ion channels in inflammatory and neuropathic pain. Issue 3 (March 2016) - Diochot, Sylvie; Alloui, Abdelkrim; Rodrigues, Précillia; Dauvois, Mélodie; Friend, Valérie; Aissouni, Youssef; Eschalier, Alain; Lingueglia, Eric; Baron, Anne
Abstract : Abstract: Mambalgins are 57-amino acid peptides isolated from snake venom that evoke naloxone-resistant analgesia after local (intraplantar) and central (intrathecal) injections through inhibition of particular subtypes of acid-sensing ion channels (ASICs). We now show that mambalgins also have an opioid-independent effect on both thermal and mechanical inflammatory pain after systemic intravenous (i.v.) administration and are effective against neuropathic pain. By combining the use of knockdown and knockout animals, we show the critical involvement of peripheral ASIC1b-containing channels, along with a contribution of ASIC1a-containing channels, in the i.v. effects of these peptides against inflammatory pain. The potent analgesic effect on neuropathic pain involves 2 different mechanisms depending on the route of administration, a naloxone-insensitive and ASIC1a-independent effect associated with i.v. injection and an ASIC1a-dependent and partially naloxone-sensitive effect associated with intrathecal injection. These data further support the role of peripheral and central ASIC1-containing channels in pain, demonstrate their participation in neuropathic pain, and highlight differences in the repertoire of channels involved in different pain conditions. They also strengthen the therapeutic potential of mambalgin peptides that are active in a broader range of experimental pain models and through i.v. systemic delivery. Abstract : Supplemental Digital Content is Available in the Text.Acid-sensing ion channel inhibitor mambalgins relieve inflammatory and neuropathic pain in mice by intravenous or intrathecal delivery through inhibition of central and peripheral acid-sensing ion channel inhibitor-1–containing channels.